Social Media Influence on Consumerism Trends Among College Students - Ayatullah Maulidy; Abdul Wahid Zaini; M Aqil Fahmi Sanjani (Indonesian Journal of Education and Social Studies, 2025)
The development of social media in the digital era has had a significant impact on individual consumption patterns, including among college students. Social media is not only a means of communication and entertainment, but also a strategic space for digital marketing practices that can shape consumer behavior on a massive scale. This study aims to analyze how social media shapes student consumer behavior in higher education, particularly in the context of campus life. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation. Data analysis is carried out in stages through data presentation, data reduction, and drawing conclusions based on an interactive model. The results show that student consumer behavior is formed through four main factors: structured and systemic influencer marketing, massive promotion through various social media platforms, the formation of virtual student communities that encourage collective consumption practices, and the Fear of Missing Out (FoMO) phenomenon that triggers social anxiety. These findings imply the importance of preventive measures to educate students to be wiser in using social media, as well as developing digital literacy that can curb the rate of excessive consumerism that has the potential to impact psychosocial conditions.